2017
DOI: 10.1002/chem.201702680
|View full text |Cite
|
Sign up to set email alerts
|

Ketone Formation from Carboxylic Acids by Ketonic Decarboxylation: The Exceptional Case of the Tertiary Carboxylic Acids

Abstract: For the reaction mechanism of the ketonic decarboxylation of two carboxylic acids, a β-keto acid is favored as key intermediate in many experimental and theoretical studies. Hydrogen atoms in the α-position are an indispensable requirement for the substrates to react by following this mechanism. However, isolated observations with tertiary carboxylic acids are not consistent with it and these are revisited and discussed herein. The experimental results obtained with pivalic acid indicate that the ketonic decar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…Intensive decarboxylation accompanying the formation of the corresponding symmetrical dialkyl ketone is observed during propionic acid pyrolysis ( Figure 1A,B) and all studied acids (C2-C10), except pivalic acid. As was previously established [19,35], and also observed it in this work, pivalic acid forms two other major products, isobutene and 2-dimethyl-4-methyl-3-pentanone (Table 1). As was previously established [43,[47][48][49], the ketenization reaction (pathway b, Scheme 3) proceeds on the silica at 300-450 • C with a high level of selectivity.…”
Section: Kinetic Studysupporting
confidence: 88%
See 2 more Smart Citations
“…Intensive decarboxylation accompanying the formation of the corresponding symmetrical dialkyl ketone is observed during propionic acid pyrolysis ( Figure 1A,B) and all studied acids (C2-C10), except pivalic acid. As was previously established [19,35], and also observed it in this work, pivalic acid forms two other major products, isobutene and 2-dimethyl-4-methyl-3-pentanone (Table 1). As was previously established [43,[47][48][49], the ketenization reaction (pathway b, Scheme 3) proceeds on the silica at 300-450 • C with a high level of selectivity.…”
Section: Kinetic Studysupporting
confidence: 88%
“…On this basis, it is concluded that alpha hydrogen atoms take part in the reaction. The second proof is that a symmetric ketone pivalone is not formed from pivalic acid (CH 3 ) 3 C-COOH) [28,30,35]. It was postulated that the reason for the lack of ketonization of pivalic acid is the absence of α-hydrogen, which excludes enolization, so ketonization is impossible [19,30,33].…”
Section: Scheme 1 Simplified Schemes Of Possible Ketonization Mechanmentioning
confidence: 99%
See 1 more Smart Citation
“…It is less likely that 13 C/ 12 C exchange can proceed through some kind of a direct alkyl group transfer from ketone to CO2 as in the concerted mechanism of ketonic decarboxylation, or via formation of alkyl radicals, or alkyl anions, given that all such options have been ruled out over the century-long debate in favor of the stepwise mechanism of alkyl group transfer via beta-keto acid formation [10][11][12]. The most recent experimental evidence against direct alkyl group transfer is that reported in the work of Oliver-Tomas et al [14]. 13 C-labeled carboxylic acids too exchange their carboxyl group presumably through the condensation between enolized surface carboxylate with CO2 into intermediate malonic acid and CO2 by the water-gas shift reaction, which is also unlikely at temperatures below 300 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Exchange via retro-Koch -Koch reaction equilibrium under chosen conditions is very unlikely. Retro-Koch decomposition of carboxylic acids requires much higher temperatures, above 500 °C, and cannot compete with the ketonic decarboxylation favored at 300 °C[14]. Only acids lacking alpha-hydrogens and not able to undergo ketonic decarboxylation may be forced into the retro-Koch reaction at extreme temperatures.…”
mentioning
confidence: 99%